Beneficial effects of ginkgetin on improving nonalcoholic steatohepatitis characterized by bulk and single-cell RNA sequencing analysis - Wang, Chaoyang; Bai, Yaowei; Li, Tongqiang; Liu, Jiacheng; Wang, Yingliang; Ju, Shuguang; Yao, Wei; Xiong, Bin; Zhou, Guofeng (Frontiers in Pharmacology, 2023)
Background and Aims: Nonalcoholic steatohepatitis (NASH) has become one of the major causes of cirrhosis and liver failure. However, there are currently no approved medications for managing NASH. Our study was designed to assess the effects of ginkgetin on NASH and the involved mechanisms.We constructed a mouse model of NASH by high-fat diet for 24 weeks. The effects of ginkgetin on NASH were evaluated by histological study, western blot, and biochemical analysis. RNA Sequencing (RNA-Seq) analysis was used to investigate the alteration in gene expression and signaling pathways at bulk and single-cell levels.Results: Administration of ginkgetin resulted in a marked improvement in hepatic lipid accumulation, inflammation, and fibrosis in the NASH model. And these results were supported by bulk RNA-Seq analysis, in which the related signaling pathways and gene expression were markedly downregulated.Furthermore, single-cell RNA-Seq (scRNA-Seq) analysis revealed that the effects of ginkgetin on NASH were associated with the reprogramming of macrophages, hepatic stellate cells, and endothelial cells. Especially, ginkgetin induced a marked decrease in macrophages and a shift from pro-inflammatory to anti-inflammatory phenotype in NASH mice. And the NASH-associated macrophages (NAMs), which emerge during NASH, were also significantly downregulated by ginkgetin.Conclusions: Ginkgetin exhibits beneficial effects on improving NASH, supported by bulk and single-cell RNA-Seq. Our study may promote pharmacological therapy for NASH and raise the existent understanding of NASH.